Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00432-010-0866-z
|View full text |Cite
|
Sign up to set email alerts
|

Palliative radiotherapy for bleeding from advanced gastric cancer: is a schedule of 30 Gy in 10 fractions adequate?

Abstract: RT with 30 Gy in 10 fractions is an adequate treatment for bleeding from advanced gastric cancer, especially in patients with poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 10 publications
(14 reference statements)
6
66
1
Order By: Relevance
“…External beam radiation therapy plays a well-defined role in the control of bleeding in patients with localized but unresectable tumors [50][51][52][53][54][55]. Palliative doses ranging from 8 Gy per single fraction to 40 Gy in 16 fractions can control the bleeding in approximately 80% of all patients [55].…”
Section: Radiotherapymentioning
confidence: 99%
“…External beam radiation therapy plays a well-defined role in the control of bleeding in patients with localized but unresectable tumors [50][51][52][53][54][55]. Palliative doses ranging from 8 Gy per single fraction to 40 Gy in 16 fractions can control the bleeding in approximately 80% of all patients [55].…”
Section: Radiotherapymentioning
confidence: 99%
“…Active bleeding is one of the most serious and fatal complications in patients with advanced gastric cancer [1][2][3][4][5]. The incidence of gastric cancer with bleeding is reported to be about 1-8 % [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective series of 30 Japanese patients with gastric cancer and persistent upper gastrointestinal bleeding reported that 22 patients (73%) responded to radiotherapy, 11 of whom (50%) experienced rebleeding (median time to rebleeding 3.3 months). 50 Patients who received chemoradiotherapy (n = 12) had a significantly lower rebleeding rate than those undergoing radiotherapy alone (36.4% versus 63.6%; P <0.001). 50 The use of radiotherapy has also been limited to symptom control in patients with node-positive gastric cancer recurrence after curative gastrectomy-because such recurrence is considered incurable-and the role of radiotherapy in this setting is not well defined.…”
Section: Palliative Radiotherapymentioning
confidence: 89%
“…50 Patients who received chemoradiotherapy (n = 12) had a significantly lower rebleeding rate than those undergoing radiotherapy alone (36.4% versus 63.6%; P <0.001). 50 The use of radiotherapy has also been limited to symptom control in patients with node-positive gastric cancer recurrence after curative gastrectomy-because such recurrence is considered incurable-and the role of radiotherapy in this setting is not well defined. However, a small retrospective study has supported a benefit of aggressive local palliative radiotherapy in prolonging the survival of patients with isolated nodal metastases.…”
Section: Palliative Radiotherapymentioning
confidence: 89%